Varied impacts on outpatient services among departments and divisions in the early phase of the COVID-19 pandemic: Implications for personnel mobilization and preparatory training. Issue 10 (30th September 2021) - Chang, Ya-Ting; Chiang, Shu-Chiung; Lee, Wui-Chiang; Chen, Tzeng-Ji; Hwang, Shinn-Jang
Abstract : Background: Coronavirus disease 2019 (COVID-19) spread all over the world in 2020. In the face of the sudden pandemic, workforce mobilization has been of critical concern to medical institutions. During the pandemic, the public's behaviors of seeking medical assistance have also changed. Using the real-world data of a large medical center in Taiwan, this study aimed to analyze the fluctuations of outpatient visits among various departments and divisions in the early phase of the COVID-19 pandemic and to provide suggestions for staff allocation in similar future events. Methods: Data of outpatient visits at Taipei Veterans General Hospital were obtained for analysis. The weekly fluctuations of outpatient visits among 36 departments or divisions were computed for 8 weeks from February 3 to March 29, 2020, the early phase of the pandemic. The monthly data of outpatient visits by department and division in March 2020 were also extracted for comparison with those in March 2019. A simple regression equation was used to calculate the weekly trends. Results: Average outpatient visits decreased by 26% in 2 months following the outbreak. Among the 36 departments or divisions, ophthalmology, orthopedics, and cardiology underwent marked declines after the outbreak; the slopes of the simple regression equation were −110.8, −100.7, and −99.2, respectively. By contrast, transfusion medicine, toxicology, transplantation surgery, pediatric surgery, chest surgery, technical aid, and oncology were divisions less influenced. In the year-over-year comparison, infection was the only department or division with positive growth (20.5%), whereas all others exhibited negative growth. Conclusion: In the future, we can fulfil the additional personnel needs during a pandemic by redeploying physicians from departments experiencing a reduced workload. Hospitals should also establish preparatory employee training programs to ensure that the reassigned personnel are adequately equipped to serve in their new positions.